2016
DOI: 10.16970/ted.20601
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal effects of mixtures of entomopathogenic fungi and synthetic insecticides on biological aspects of Musca domestica L.

Abstract: Lethal and sublethal effects of mixtures of entomopathogenic fungi and synthetic insecticides on biological aspects of Musca domestica L.Entomopatojen fungus ve sentetik insektisit karışımlarının Musca domestica L.'nın biyolojik dönemleri üzerinde lethal ve sublethal etkileri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…These results explain why insects lost bodyweight after being exposed to an insecticidal sublethal dose in this investigation. Reduction of AD, RGR, and ECD due to insecticidal subtethal doses exposure have either a direct or indirect relation with an insect's fertility and longevity, making them too weak against diseases and natural enemies [50,51]. Thus, we observed that the nutritional indices (i.e.…”
Section: Effect Of Sublethal Doses Of Insecticides On Nutritional Ind...mentioning
confidence: 83%
“…These results explain why insects lost bodyweight after being exposed to an insecticidal sublethal dose in this investigation. Reduction of AD, RGR, and ECD due to insecticidal subtethal doses exposure have either a direct or indirect relation with an insect's fertility and longevity, making them too weak against diseases and natural enemies [50,51]. Thus, we observed that the nutritional indices (i.e.…”
Section: Effect Of Sublethal Doses Of Insecticides On Nutritional Ind...mentioning
confidence: 83%
“…In contrast, only eight publications contributed with approximately half the combinations with the top four contributing with 41%. This gives the dataset a very strong bias towards the chemicals, parasites and hosts used in these four publications 41 44 .…”
Section: Resultsmentioning
confidence: 99%
“…This combination also led to a reduced level of fungal inoculum needed to cause high levels of mortality in the test groups. Combinations of sublethal doses of six different insecticides with B. bassiana conidia caused a higher mortality than when the fungus was used alone, except with bifenthrin and fipronil (Farooq and Freed 2016). In several combinations, adult longevity and fecundity, egg hatching, percentage pupation, and pupal weight were all reduced.…”
Section: Other Biting and Nuisance Fliesmentioning
confidence: 93%
“…Another technique to delay resistance development and optimize the impact of BCAs is to use a combination of active ingredients. EPF have been shown to be compatible for use with other pesticides, such as B. bassiana and acetamiprid, emamectin, imidacloprid, and lufenuron (Farooq and Freed 2016), or M. anisopliae and deltamethrin (Bahiense et al 2008), imidacloprid (Paula et al 2011b), neem (Gomes et al 2015), and spinosad (Sharififard et al 2011). Compatability between EPNs and imidacloprid (Koppenhöfer et al 2000) and clorfenvinfos (Reis-Menini et al 2008) also has been demonstrated.…”
Section: Integrated Pest Management and The Use Of Combined Biological Control Agentsmentioning
confidence: 95%